2019
DOI: 10.13004/kjnt.2019.15.e29
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular hematoma on the psoas muscle

Abstract: Intramuscular hematomas on the psoas muscle are rare and usually occur as a result of trauma, iatrogenic etiology during lumbar surgery, rupture of the aortic aneurysm, and hematologic diseases. The incidence of spontaneous psoas muscle hematomas has slowly increased as a result of using anticoagulation and antiplatelet agents. Magnetic resonance (MR) imaging is a more sensitive option compared to computed tomography (CT) when diagnosing a hematoma. Coronal T2-weighted images are more useful. CT imaging is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…The risk of development of iliopsoas hematoma after anticoagulation therapy has been discussed by multiple authors. 1,28,29 Sarwat et al reported a case of a 31-year-old female with intractable lower back pain, who underwent a dynamic stabilization procedure from L3 to L5. Post-operatively she received prophylactic anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of development of iliopsoas hematoma after anticoagulation therapy has been discussed by multiple authors. 1,28,29 Sarwat et al reported a case of a 31-year-old female with intractable lower back pain, who underwent a dynamic stabilization procedure from L3 to L5. Post-operatively she received prophylactic anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…Most of iliopsoas hematomas are managed conservatively if there was no clinical and hemodynamic deterioration. 1,31 This can include stopping anticoagulants, fluid and blood administration and close observation with monitoring of hemoglobin and coagulation profile. 32 However, surgical intervention is recommended by others in case of hemodynamic instability despite resuscitation and neurological deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoas muscle hematoma is defined as a spontaneous or traumatic retroperitoneal collection of blood involving the psoas muscle [ 2 ]. Hematomas on the psoas muscle occur secondary to trauma, leaking abdominal aortic aneurysms, iatrogenic etiology during lumbar surgery including endoscopic discectomy, recent biopsy, tumor, use of anticoagulants, or coagulation disorders such as disseminated intravascular coagulation and hemophilia [ 3 , 4 ]. As a general rule, coagulopathies and trauma are etiologic factors in the younger population while anticoagulant therapy and aortic aneurysm rupture assume prominence in the older age range [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether incidental diagnosis is frequent, clinical presentation depends on the severity of the hemorrhage, varying from compressive symptoms, such as groin or thigh pain, muscle dysfunction, numbness or paresthesia of the unilateral lower extremity, and occasionally nerve palsy with the femoral nerve involvement and anemia [ 1 , 2 ]. Ecchymosis in the periumbilical area (Cullen’s sign) or in the flanks (Grey-Turner's sign) may occur [ 3 ].…”
Section: Introductionmentioning
confidence: 99%